Peer-Led Neonatal Resuscitation Training: Experience of Kairuki University - Raidah R Gangji; Leonard Malasa; Gambuna D Koya; Aliasgar Khaki; Felician Rutachunzibwa; Maulidi Fataki; Florence Salvatory Kalabamu; Esther M Johnston; Esther Mwaikambo (Journal of Medical Education and Curricular Development)
Background Neonatal mortality remains a significant public health concern in Tanzania, with birth asphyxia being one of the leading causes. The Helping Babies Breathe program aims to equip providers with essential neonatal resuscitation skills, particularly in resource-limited settings. Objective To assess and document the effectiveness of a peer-led training program on knowledge and confidence in neonatal resuscitation. Methods Helping Babies Breathe-Kairuki University (HBB-KU) initiative; a student-led program including both theoretical and practical components attended by future and current healthcare professionals (HCPs). Pre- and post-training knowledge tests assessing knowledge and understanding, and self-evaluation tests reporting self-confidence were administered. Results Test results of participants from 2016 to 2023 were analyzed using the paired t -test. HBB-KU initiative successfully trained 1389 trainees. A total of 1243 (93.11%) included medical, nursing, and other health-allied science students. Pre (10.63 ± 2.53) and post (14.71 ± 1.60) training knowledge test scores demonstrated statistically significant ( P  < .01) improvements. Confidence prior to training, 213 (15.97%) participants reported feeling “very confident”; however, following training, an increase was noted, reaching 784 (58.72%) participants feeling “very confident,” demonstrating a difference of 42.75%. Conclusion The results indicate HBB-KU peer-led training initiative is effective in mitigating knowledge gaps and developing confidence around neonatal resuscitation among participants. Given the resource-limited setting, this accomplishment provides a context for a replicable model where students can teach and train peers, and practicing HCPs may be an efficient method to expand neonatal care in similar circumstances, globally.